“Sound Come-Unity”: Hafez Modirzadeh and the Role of Intercultural Improvisation in Decolonial Pedagogy and Praxis - Panikker, Dhiren (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Recent scholarship examines how improvisational pedagogy can model ethical social practices and relations (Heble and Waterman 2008). A parallel strain of literature highlights the importance of decolonizing Western knowledge systems through more global pedagogies (De Lissevoy 2010; Nakata 2012). Little work, however, considers the role of improvisation in decolonizing the institution. In this essay, I examine the role of intercultural improvisation as a critical decolonial pedagogy and practice within the neoliberal university through an auto-ethnographic reading of my experience as performer in the ImprovisAsians! 2017 Festival. Hosted by Asian Improv ARts, a pan-Asian musical collective dedicated to Asian American activism and community building, this week-long festival brought together artist-scholars of color for a series of collaborative performances and discussions on the campus of San Francisco State University, the generative site of the 1968 Third World Liberation Front Strikes (TWLF). Almost fifty years later, this institutional space was my entry point into what Asian Improv artists Francis Wong and Hafez Modirzadeh describe as their “sound come-unity,” an ethical collective built and sustained through musical sound. Following George Lewis’ call for an improvisational pedagogy as critical methodology (2008), I explore the musical intimacies and listening strategies of this particular “sound community” within the context of discourses on academic diversity and inclusion. I argue that intercultural improvisation serves as a site of fugitive planning and collaborative study with the potential to decolonize institutional epistemologies.